ANALISIS PENGARUH RASIO KEUANGANTERHADAP KINERJA BANK UMUM SYARIAH (Studi pada Perbankan Umum Syariah yang Terdaftar di BI Tahun 2012-2016) - nur mayunita (MAGISTER MANAJEMEN UNISMA, 2020)
The purpose of this study is: to test How the overall picture of the ratio of the financial period of 2012 to 2016 How the effect of capital asset quality, profitability, liquidity to the performance of sharia commercial banks.The sample used in this research is banking company of sharia bank which is registered in bank indonesia as well as present financial report for period 2012-2016. The results of this study show that in this study, the financial ratios of CAR, and BOPO, for syariah commercial banks have significant effect on ROA, while NPF and LDR have an effect on ROA but not significant on the profitability of sharia foreign exchange bank in Indonesia and using camel minus management method with 4 variables. Keywords: ROA, CAR, NPF, ROA, and LDR